OPTIMASI METODE EKSTRAKSI CAIR-CAIR SENYAWA-SENYAWA PADA TABLET EKSTASI DITENTUKAN DENGAN SPEKTROFOTODENSITOMETER - Putra, Ida Bagus Gde Agung Raditya Eka; Laksmiani, Ni Putu Linda; Widjaja, I.N.K. (Indonesian Journal of Legal and Forensic Sciences (IJLFS), 2015)
A research concerned on liquid-liquid extraction method optimation has been carried out. The optimation was held to choose the extraction solvent and variation of pH. The simulation solution which contained methylendioxy methampethamine, methampethamine, ketamine, and amitryptiline as the internal standard were analyzed by TLC-Spectrophotodensitometry. The extract was spotted on TLC Si 60 G F254 chromatography plate, then eluted by TB mobile phase (cyclohexhane : toluene : dietylamine = 75:15:10). The chromatography plate was scanned at 202 nm. The chromatogram was analyzed based on the ratio between the area under curve (AUC) of the analyte and the AUC of the internal standard. The concentration and the recovery of the extract was determined. The simulation solution was extracted into chloroform and toluene solvent, the best solvent was selected. The selected solvent (chloroform) was used to extract the sample in pH range 10-12. The pH 11.5 was the best condition to extract the sample. The result showed that the optimum liquid-liquid extraction of the compounds on ecstasy was chloroform as the solvent with pH 11.5. This optimum condition give recovery of MDMA (99.192%), MA (98.203%) and ketamine (88.114%).